The postmistress - Blake, Sarah, 1960- (Amy Einhorn Books/G.P. Putnam's Sons, 2010)
In London covering the Blitz with Edward R. Murrow, Frankie Bard meets a Cape Cod doctor in a shelter and promises that she'll deliver a letter for him when she finally returns to the United States. Filled with stunning parallels to today's world, "The Postmistress" is a sweeping novel about the loss of innocence of two extraordinary women--and of two countries torn apart by war.